Application of Tai-Type Cooperative Learning To Increase Master Of The Concept Of Lines And Series Of Students Of Class Xi Mipa 2 SMAN 1 Sinjai - Rusliawaty Rusliawaty (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This research was at a time to find out the learning activity increase and the Math learning result through the application of Team Assisted Individualization (TAI). The subjects of this research were 32 students of Class XI MIPA 2 SMA Negeri 1 Sinjai. This research used qualitative approach that employed Class Action Research done in two cycles. Every cycle consists of planning, treatment, observation and reflection. The data collection were done by pre-test, post-test, and the students activity observation. The data collected were processed using descriptive statistics using percentage. every cycle was considered successful if in average the students scored >65 and the classical learning success was >75%. On the 1st meeting of the cycle I, the students activity which considered. Good was 28.1% and on the 2nd meeting which considered Good was 46.9%. The students' Math learning result on the cycle I that reached the minimum success criterion (KKM=65) was 81.25% or 26 out of 32 students, 6 students still could not pass the KKM needed. On the 1st meeting of the Cycle II, the students learning activity considered Good was 71.875%, on the 2nd meeting the students learning activity considered as Good and Very Good was 84.4%. The students' Math learning results also increased significantly. All the students passed or surpassed the KKM target. Therefore, it is concluded that the application of Cooperative Model Team Assisted Individualization (TAI) type to the students of XI MIPA 2 SMA Negeri 1 Sinjai has successfully reached the performance indicator on the Cycle II.